Marketing justification of introducing the original herbal medicine for the treatment of mastopathy to the pharmaceutical market of Ukraine - Zuikina, Svitlana; Palivoda, Polina (Annals of Mechnikov's Institute, 2023)
Introduction. Scientific forecasting of the need for the development of an original herbal medicinal products (MP) for the treatment of mastopathy is based on the needs of the population for an affordable and effective medicinal product that has a lower toxic effect on the human body, has a significantly smaller number of contraindications, pronounced side effects, despite the therapeutic effect occurring more slowly, the effect is steady and long-term. Aim and objectives. The aim of our work is the marketing justification of the development of an original medicinal product (MP) based on medicinal plant raw materials for the treatment of mastopathy in the form of granules. Methods. Data from the State Drug Register of Ukraine and information-reference publication "Compendium", websites of leading pharmaceutical manufacturers of Ukraine are used in the work. Based on the recommendations and standards of mastopathy therapy, the main directions of treatment and, accordingly, the group of drugs used are determined. Marketing research of the drug market of Ukraine was conducted regarding the availability of medicinal products (MP) and dietary supplements (DS) according to the corresponding therapeutic effects. The analysis was carried out according to the main active substances (international non-proprietary name (INN), dosage forms (DF), producing countries. The methods used are systematic, logical, complex, graphic. Results. An algorithm for marketing justification of the feasibility of developing and launching an original herbal medicinal product into production was developed, the components of the competitiveness of the medicinal product were selected by groups: pharmacotherapeutic, safety advantages, technological advantages. Conclusion. Conducted marketing studies of the drug market of Ukraine demonstrated the following: taking into account the increase in the number of patients with mastopathy, the development of an original medicinal product based on plant raw materials of complex action in the form of granules, with the possibility of long-term use, an appropriate level of bioavailability, economically justified and affordable is expedient and relevant. Key words: mastopathy, marketing research, original herbal medicinal products, granules.